A little less talk, a little more action: a dialogical approach to cognitive therapy. (2019) - Pugh, Matthew
Abstract: Reappraisal strategies such as 'thought challenging' and 'cost-benefits analysis' are a hallmark of cognitive therapy, but sometimes fail to bring about lasting changes in the cognitive-affective structures underlying psychopathology. Modern theories of information processing suggest that experiential, action-based interventions such as chairwork may be a more efficacious route to cognitive modification. Based upon this hypothesis, a 'dialogical' approach to cognitive therapy is presented, which aims to bring about change through evocative, here-and-now interactions with parts of the self (self-to-self dialogues) and other individuals (self-to-other dialogues). Implementation principles and facilitation skills which guide this approach are outlined. To illustrate how dialogical interventions are utilized in clinical practice, chair-based strategies for socializing clients to the cognitive behavioural model, restructuring cognitions, facilitating emotional processing, resolving ambivalence, addressing distressing memories, building character strengths, and overcoming therapeutic impasses are described. Key learning aims: As a result of reading this paper, the reader should: (1) Understand the limits of 'standard' cognitive techniques. (2) Appreciate some of the advantages of experiential methods of intervention, namely chairwork. (3) Learn how dialogical interventions are conceptualized, implemented, and facilitated in cognitive therapy.